Developing a Model of Thematic / Character Analysis toEnhance the Literary Comprehension skills,Narrative Transportation, andMetacognitive Awareness of Reading Strategies of EFL Student Teachers at the Faculty of Specific Education - Ahmed, Eman El SayedSayed; El-Naggar , Bahaa El-Din El-Sayed (International Journal of Psychosocial Rehabilitation, 2020)
The current study was conducted to investigate the effect of aninstructional thematic/character analysis model on enhancing the literary comprehension skills, narrative transportation, and metacognitive awareness of reading strategies of EFL student teachers at the Faculty of Specific Education. The one group pre-posttest research design was adopted to achieve the research objectives. The study sample consisted of fifty second-year EFL majors whowere selected by simple random sampling. Instruments of the study included aliterary comprehension test, a narrative transportation scale and a survey of reading strategies. The experimental treatment lasted for 11 weeks during the first semester of the academic year (2019-2020). Over 25 sessions, the students received training on the implementation of the thematic/character analysis model throughout the introduction to literary analysis training course, which was designed and implemented by the researcher. The data obtained from the pre- and post-administrations of the study instruments were analyzed using descriptive statistics and t-tests.The study results indicated that there were statistically significant differences between the mean scores of the study sample on the pre and post administrations of the literary comprehension test, the narrative transportation scale and the survey of reading strategies at 0.01 level of confidence in favor of the post administrations.This confirmed that the suggested model had a positive effect on fostering the participants’ literary comprehension skills, narrative transportation and metacognitive awareness of reading strategies. Discussion of these findings, recommendations and suggestions for further research were presented.